Chrześcijańskie wartości europejskie. Geneza, znaczenie i oddziaływanie = Christian values in Europe. Origins, meaning and effects - Królikowski, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The question of values considered from the European perspective constitutes a subject for debates and is contemporary discussed in reference to many different scientific fields (history, anthropology, philosophy, theology) as well as in political circles especially in the context of European Union, which as a result affects decisions (not always right) influencing life of the people in Europe.
Keywords: Europa; wartości; chrześcijaństwo; Unia Europejska; integracja europejska; kultura; wolność; godność człowieka; humanizm; oświecenie; romantyzm; Europe; values; Christianity; European Union; European integration; culture; freedom; human dignity; humanism; Enlightenment; romanticism